PENGARUH APLIKASI LINE TERHADAP HUBUNGAN ANTARPRIBADI DI KALANGAN MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE ANGKATAN 2010-2013 - Siti Meisyaroh (Jurnal Komunikasi dan Bisnis, 2018)
At this time, the growing communications technology in human life. These developments make it easy for people to communicate with each other without being limited by distance. LINE instant messenger app now become a medium of communication within the individual interpersonal relationships. However, until now there has been clearly known to significantly influence the LINE app on interpersonal relationships. The main theory used in this study is the Media Ecology theory. The results showed that there is a positive influence of the LINE application as part of a media ecology and the use of LINE application as a medium of interpersonal relations among students in Communication Studies Program Institute of Business and Informatics Kwik Kian Gie Class of 2010-2013. This can be seen through the overall average values of 3.96 and 3.89 which shows that the majority of respondents agreed to the statement in the questionnaire. The results also found that LINE applications can improve intimacy in interpersonal relationships, self-made individuals more open to other people, and reduce losses due to miscommunication. The results obtained conclude that the application of LINE has a positive influence and has a strong relationship to the interpersonal relationships among student’s class of 2010-2013. Keywords: Instant Messenger, Interpersonal Relationships, Communications Technology